Incidental diagnosis of intraductal papillary neoplasm of the bile duct: Imaging findings from a case report - Imene Chafai, MD; Alba Igual-Rouilleault, MD PhD; Morgane Van Wettere, MD (Radiology Case Reports, 2025)
Intraductal papillary neoplasms of the bile ducts (IPNBs) represent a rare biliary tract tumors with malignant potential, requiring surgical resection to prevent progression to cholangiocarcinoma. In this case, an 83-year-old woman with an obstructive pattern in liver function tests was incidentally found to have a solid mass in the left hepatic lobe on ultrasound. Liver MRI suggested a polypoid intraductal papillary neoplasm of the left bile duct, and histopathological analysis after surgical resection confirmed low-grade dysplasia with a pancreaticobiliary subtype. Postoperative MRI showed no residual tumor, and the patient remains under close observation with no evidence of recurrence. This case highlights the importance of imaging techniques in the early detection and characterization of IPNB, and includes a summary of its morphological subtypes.